Problems and possibilities of wheat-maize somatic hybridization - Göntér, Ildikó (Acta Biologica Szegediensis, 2002)
Protoplast fusion was performed between mesophyll cells of wheat (Triticum aestivum L.) and albino maize (Zea mays L.) by polyethylene glycol (PEG) treatments. The parental protoplasts were not able to produce green plants without fusion. The hybrid calli have mixed cytoplasm and regenerated green, maize-like plants, six months after the PEG treatment. The plants were sterile although had both female and male flowers. The RAPD analysis (using total DNA, and three primer combinations) produced bands resembling the wheat profile. The cytological analysis revealed 56 chromosomes in the root tip and callus cells, but intact wheat chromosome was not observed. Genomic in situ hybridization using total wheat DNA as probe revealed the presence of wheat DNA droplets in the maize chromosomal background. The flow cytometrical analysis showed intermediate DNA concentration in hybrid nucleus. Other intermediate morphological traits of plants with hybrid origin were not found.